A somatotrofina bovina recombinante sobre a ovulação, condição corporal e níveis séricos de colesterol e glicose em ovinos - Castro, Andréa Azevedo Pires de (2001)
The aim of the present study was to investigate if the rBST was able to improve ovulation rates in ewes syncronizated with progesterone and also to verify its effects on cholesterol and glucose metabolism (experiment one) and to evaluate weight gain in lactating ewes and their products (experiment two). Ewes were treated with 3mg/kg of rBST in the first experiment and 4mg/kg in the second. Ovulation rates were 0.9 ± 17951 for the control group and 1.18 ± 0,121968 for the treated group, and were not statisticaly different. Additionally, no differences between the groups were found in glucose and cholesterol serum levels in the first experiment. On the second experiment body conditions scores in the treated group were decreased between days 1 to 10 and then increased between days 10 to 20 (p<0,05). Weight gain of lambs and ewes and body condition scores variations between days 1 and 20 were not different. In conclusion, rBST is not able to affect ovulation rates or energy metabolism in ewes. However its use can affect ewes body condition scores at the beggining of the treatment.